Study of the 234,236U(n,f) and 232Th(n,f) cross sections in the energy range between 14.8 and 19.2 MeV with Micromegas detectors - Chasapoglou, S.; Michalopoulou, V.; Stamatopoulos, A.; Kalamara, A.; Kokkoris, M.; Vlastou, R.; Lagoyannis, A.; Eleme, Z.; Patronis, N. (HNPS Advances in Nuclear Physics, 2019)
The design of fast nuclear reactors and accelerator driven systems is very strongly based on the accurate knowledge of neutron-induced fission cross sections on several actinides, such as 234,236U and 232Th. Specifically, these isotopes play an important role in the thorium cycle. Regarding (n,f) reactions on these isotopes (namely 234,236U(n,f)), few available discrepant cross-section datasets exist in literature in the energy range between 14-20 MeV, accompanied by relatively large errors, resulting to poor evaluations. In the present work, the study of the fission cross sections of the 234,236U and 232Th was possible with the use of quasi-monoenergetic neutron beams at 14.8, 15.2, 17.8 and 19.2 MeV at the 5.5 MV Tandem Van de Graaff accelerator of NCSR “Demokritos”, produced via the 3H(d,n)4He reaction. Moreover, a methodology is presented for the estimation of the parasitic neutrons present in the experimental area, for facilities with no complementary time-of-flight installation.